Proceedings of the 2021 AERA Annual Meeting 2021
DOI: 10.3102/1681137
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Prosocial Behavior Protects Against Academic Risk in Neighborhoods With Low Socioeconomic Status

Abstract: including the URL of the record and the reason for the withdrawal request.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Helping the family with chores may mitigate academic risks associated with low socioeconomic status (e.g., resource limitations and barriers to accessing enrichment opportunities). Consistent with this finding, two prior studies of predominantly White and South Asian children (ages 4–10) found that those from low‐income communities showed higher levels of academic performance and behavioral regulation if they helped others more often, compared to if they helped others less (Armstrong‐Carter, Miller et al., 2021; Flouri & Sarmadi, 2016). The current study extends this prior research by demonstrating that helping with chores may also be protective against academic risk associated with low socioeconomic status among Black adolescents.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Helping the family with chores may mitigate academic risks associated with low socioeconomic status (e.g., resource limitations and barriers to accessing enrichment opportunities). Consistent with this finding, two prior studies of predominantly White and South Asian children (ages 4–10) found that those from low‐income communities showed higher levels of academic performance and behavioral regulation if they helped others more often, compared to if they helped others less (Armstrong‐Carter, Miller et al., 2021; Flouri & Sarmadi, 2016). The current study extends this prior research by demonstrating that helping with chores may also be protective against academic risk associated with low socioeconomic status among Black adolescents.…”
Section: Discussionsupporting
confidence: 54%
“…Alternatively, adolescents from low‐income families who provide more support to the family could be protected from contextual challenges typically experienced in low‐income homes (e.g., neighborhood crime, resource deprivation), because supporting the family can serve to integrate youth more fully into the family system and create mutually beneficial, shared support networks (Cross, Taylor et al., 2018). Consistent with this notion, a few studies have shown that youths’ prosocial behavior to peers can be protective against educational and behavioral risk in contexts of adversity, in predominantly White and South Asian samples (Armstrong‐Carter, Miller, et al., 2021; Flouri & Sarmadi, 2016). Given the importance of support networks within Black adolescents’ families, and the variability in socio‐economic status within the Black population, it is important to examine how the interplay between Black adolescents’ provision of support to the family and household income relates to their educational success.…”
Section: Introductionmentioning
confidence: 89%
“…However, caregiving is also common in middle 7 and even early childhood. 26 When more information is available about the prevalence of caregiving youth below age 10, future research may include younger children in estimates of caregiving youths' economic impact.…”
Section: Limitationsmentioning
confidence: 99%